“Even though Doctor has Advised to Practice Foot Care I have not Practiced Soaking Feet in Lukewarm Water so Far” Self-care Practices, Enablers, and Barriers: A Mixed Methods Study among Individuals with Diabetes from a Rural Area of South India - Abhay S. Nirgude; TM Revathi; Nagendra Navya; Poonam R. Naik (Indian Journal of Community Medicine)
Background: Self-efficacy is the ability by which a person confronts problems in day-to-day life with goal- centered attitude. The clinician plays a vital role in promoting self-care though a series of social, cultural and economic factors also contribute positively towards it. This study was conducted to assess the self-care practices among diabetic individuals aged 30 years and above and to understand its enablers and barriers. Materials and Methods: Explanatory mixed method study was conducted from August 2018 to October2020. Quantitative assessment was done wherein a questionnaire was administered to 297 study participants enrolled by simple random sampling followed by in-depth interviews by purposive sampling as qualitative component. Multivariate logistic regression analysis was used to study the relationship of independent variables with various domains of self- care practice. P value <0.05 was considered as statistically significant. Results: Study found educational status, occupation and religion had a statistically significant association with self-care practices. Regular physical activity, good dietary practices and family support were a few enablers, whereas lack of awareness, time constraints, co-morbidities and environmental factors were some of the barriers to self-care practice. Conclusions: In the present study, self-care practice in terms of diet and physical activity were found to be good whereas blood sugar level monitoring and foot care practices were poor.